File Management Application with AI Assistance - Aiman Hazriq Shazwan; Mohd Zanes Zahid (Applied Information Technology And Computer Science, 2026)
With the increasing reliance on mobile devices for everyday tasks, file management has become a critical challenge, particularly for non-technical users who struggle with complex systems. This project aims to develop an AI-enhanced file management application tailored for Tiang Seri Sdn. Bhd., which automates tasks such as file naming, and categorization, and storage optimization. The application leverages AI to offer intelligent suggestions and simplify file organization, making it easier for users to manage their documents. The system was developed using Flutter, focusing on an intuitive interface and efficient workflow. Preliminary testing indicates that the app significantly improves file organization, reduces cognitive load, and enhances overall productivity. Future work will focus on further refining AI capabilities and expanding the app’s features for broader business applications.